Medical care for children on the autism spectrum - Wiesner, Elizabeth (Henry Stewart Talks, 2020)
Screening, diagnosis and services, Medical care issues, Medical home, Helping medical visits succeed, Common medical problems, Genetics and autism, Eating, sleeping and safety issues, Seizures, Medication, Hospital and emergency department use, Legal issues, Useful apps